2019
DOI: 10.1163/22134468-20191149
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure of Zimbardo Time Perspective Inventory (ZTPI) in a Norwegian Convenience Sample

Abstract: Sense of time is a fundamental aspect of human psychology. The Zimbardo Time Perspective Inventory (ZTPI) is a widely used questionnaire meant to measure fundamental experiential dimensions of time, such as past, present and future. The aim of this study was to establish model fit of a Norwegian extended version of the ZTPI. The study is based on a convenience sample of 713 individuals. Based on previous findings, we employed confirmatory factor analysis and exploratory structural equation modelling to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 42 publications
(43 reference statements)
1
9
0
Order By: Relevance
“…There is no comparison data for TTPI among cancer patients as this study is the first. Compared with other groups, however, the mean results in the sample (3.4) are still higher that TTPI scores of healthy Norwegian adults (3.19) ( Skogen & Nesvåg, 2019 ), Portuguese students (2.84) ( Ortuño & Echeverría, 2013 ), and Dutch people with suicidal tendencies (3.25) ( Van Beek, 2013 ). One may speculate that this is due to the Polish population’s high level of catholic religiosity.…”
Section: Discussionmentioning
confidence: 75%
“…There is no comparison data for TTPI among cancer patients as this study is the first. Compared with other groups, however, the mean results in the sample (3.4) are still higher that TTPI scores of healthy Norwegian adults (3.19) ( Skogen & Nesvåg, 2019 ), Portuguese students (2.84) ( Ortuño & Echeverría, 2013 ), and Dutch people with suicidal tendencies (3.25) ( Van Beek, 2013 ). One may speculate that this is due to the Polish population’s high level of catholic religiosity.…”
Section: Discussionmentioning
confidence: 75%
“…The above-mentioned findings may be put into question because ZTPI suffers from low reliability. Although the original paper by Zimbardo and Boyd (1999) reports acceptable values of internal consistency, later studies revealed serious reliability problems (Worrell & Mello, 2007), particularly in the samples investigated outside the USA (e.g., Akirmak, 2019;Skogen & Nesvåg, 2019). Moreover, confirmatory factor analysis shows poor indices of fit concerning the original five-factor structure of ZTPI (Worrell & Mello, 2007).…”
Section: Time Perspective As a Psychological Traitmentioning
confidence: 95%
“…However, its most distinctive feature is that it allows the testing of different models without imposing zero-order constraints on item loading on non-target factors. This technique has been employed successfully in testing the construct validity of the five-factor model of personality (e.g., Marsh et al, 2010Marsh et al, , 2013, similar measures across contexts (Furnham et al, 2013), as well as the ZTPI (e.g., Skogen and Nesvåg, 2019). The interpretation of fit indices in ESEM is based on the same cutoff values as in CFA; values higher than .90 for CFI and lower than .05 for the root mean square error of approximation (RMSEA) indicate an acceptable goodness of fit (Asparouhov and Muthén, 2009).…”
Section: Exploratory Structural Equations Modelingmentioning
confidence: 99%